2022
DOI: 10.1155/2022/1111488
|View full text |Cite|
|
Sign up to set email alerts
|

Animation Narrative on Stress Relief and Psychological Cognitive Development in Adolescents

Abstract: As the atmosphere of domestic animation is getting stronger and stronger in recent years, its proportion in the process of public aesthetics, entertainment, and consumption is increasing; thus, the relationship between the audience and works has become an important academic focus. The theatrical animation in the animation industry has become the category that needs to be focused on and changed in the development process of domestic animation because of its characteristics of receiving attention from all-age au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%